아테네 헌장(1931)의 재고 - 최병하; Choi Byung-Ha (건축역사연구, 2012)
This paper is to review the conclusions of the Athens conference that has so far contributed to the conservation world. It is normally called the conclusions of the Athens conference as the Athens charter. But the conclusions of the Athens are not as same as the Athens Charter regarding the contents. The former had more valuable contents than the latter regarding historic monuments. And the report of the Athens conference including 56 articles and 500 pages with 55 photos was published in 1933 by the International Museums Office. But little attention has been given to the report of the Athens conference. Therefore the point I want to make is to review to the report in order to understand the agenda of the conference and to examine the Anastylosis in Acropolis. In conclusion, these agendas and the articles in the report show us that the conference was sort of milestone with some advanced modern philosophical and technical concepts about conservation and restoration of historic monuments. Also when the term of anastylosis turns to reconstruction in archaeological sites, we are going to face with the problems of authenticity.